(untitled) (The International Journal for Scientific Research, 2023)
Often we study Western philosophy and its theories with fascination about the extent of knowledge and development of Western civilization. However, there should be reasonable thinking about how the West would have reached such civilization after having been in ignorance and darkness for more than ten centuries. This paper addresses the relationship between the most applicable contemporary legal systems in the world (the French Civil and English Common) with Islamic jurisprudence. The paper aims to discuss the interaction of the West and Westerns, whether through the east (Abbasid Caliphate, the Ottoman Empire as well as the Crusades) or through the west (the Umayyad Caliphate in Andalusia and Sicily). The question that the study is trying to answer is whether the convergence between the borders of the Islamic and European countries, and commercial contacts as well as wars between them had led to the knowledge exchange? Had the Islamic Knowledge transferred to the West during ten centuries of the Islamic renaissance over ten centuries as it has transferred from the West to the Islamic states during the contemporary European Renaissance? However, some writers presume there is a correlation between both systems (Islamic and Western) on the grounds that both are heavenly based. Some other assume that the Western laws originated from Islamic jurisprudence, while and there are some who deny any connection or correlation between both systems. This study seeks to determine what and how this interaction started and grew up. It aims to focus on the legal scope not social, political, or other fields of arts. The study also will provide some specific examples that are required to answer the above questions.